2016
DOI: 10.1002/ehf2.12106
|View full text |Cite
|
Sign up to set email alerts
|

Subacute right heart failure revealing three simultaneous causes of post‐embolic pulmonary hypertension in metastatic dissemination of breast cancer

Abstract: A 72‐year‐old woman with history of breast cancer only treated surgically was referred to our department for pulmonary hypertension (PH) suspicion. Echocardiogram revealed elevated right ventricular systolic pressure. Computed tomography (CT) angiogram showed no pulmonary embolism (PE), but lung scan revealed two ventilation‐perfusion mismatch areas. Right cardiac catheterization established precapillary PH. Despite treatment with PH specific therapy (sildenafil, ambrisentan, and epoprostenol), her condition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nearly half of PTTM patients had an enlarged right heart (7). Vincent et al (17) reported that a PTTM patient whose ECG showed normal right ventricular systolic pressure in the initial stage had significantly increased two months later. Their right ventricle was moderately enlarged with good right ventricular systolic function, no right ventricular hypertrophy, and no left atrial enlargement.…”
Section: Features Of Imaging and Ultrasoundmentioning
confidence: 99%
“…Nearly half of PTTM patients had an enlarged right heart (7). Vincent et al (17) reported that a PTTM patient whose ECG showed normal right ventricular systolic pressure in the initial stage had significantly increased two months later. Their right ventricle was moderately enlarged with good right ventricular systolic function, no right ventricular hypertrophy, and no left atrial enlargement.…”
Section: Features Of Imaging and Ultrasoundmentioning
confidence: 99%
“…Perfusion studies may demonstrate defects and pathological studies with cytology and biopsy percutaneously or surgically may help in some cases [28]. Apart from supportive treatment and chemotherapy for the underlying malignancy, no specific treatments are available to withhold this fatal complication with most patients are dying shortly after diagnosis [29]. It is important to consider PTTM as a cause of unexplained dyspnea with malignancy and on the other side to look for undiagnosed cancer in patients presenting with pulmonary hypertension possibly due to PTTM.…”
Section: Pulmonary Tumour Thrombotic Microangiopathymentioning
confidence: 99%